Characterization and discrimination of selected chicken eggs in China's retail market based on multi-element and lipidomics analysis. (December 2019) - Mi, Si; Shang, Ke; Zhang, Chun-Hui; Fan, Yu-Qing
Abstract: The present study focuses on the differentiation of Deqingyuan (n = 90), Taihe (n = 90) and crossbred (n = 90) black-boned silky fowl eggs based on chemometrics analysis of multi-element and lipidomics data. A total of 53 chemical elements were simultaneously quantified in the eggs using inductively coupled plasma mass spectrometry. Multivariate statistical analysis of element data screened 30, 13 and 12 candidate discriminants for whole egg, egg yolk and egg white samples, respectively. Moreover, we utilized an LC-MS/MS-based lipidomics approach to profile lipids in the three types of egg yolks. In total, 1633 lipid species (including 43.78% glycerophospholipids, 25.66% glycerolipids, 16.66% fatty acyls, 6.86% sphingolipids, 4.10% sterol lipids, 1.53% polyketides, 1.10% prenol lipids and 0.31% saccharolipids) were consistently detected in all samples. A partial least squares discriminant analysis model was established based on the lipidomics data, which enables a 100% correct classification of the egg yolks. Using a cutoff of variable importance in projection value >1 and p value <.05, a panel of 22 potential lipid markers was discovered for the discrimination of Deqingyuan, Taihe and crossbred egg yolks. These results could facilitate a better understanding of the nutritional qualities of the evaluated eggs. Our method of combining chemical analysis with chemometrics offers a convenient and powerful tool to distinguish commercially-available eggs. Graphical abstract: Unlabelled Image Highlights: A total of 53 elements were simultaneously quantified in the eggs using ICP-MS. Multi-element profiles clearly differ among different groups of egg samples. LC-MS/MS-based lipidomics identified 1633 lipid species in all egg yolk samples. A panel of 22 lipids was screened as potential markers for the egg yolks. Chemometrics analysis of chemical composition is feasible for egg discrimination.